2021
DOI: 10.1007/s00268-021-06230-0
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic Steatosis is Associated with an Increased Risk of Postoperative Infections and Perioperative Transfusion Requirements in Patients Undergoing Hepatectomy

Abstract: Background To determine the impact of hepatic steatosis on perioperative outcomes of patients undergoing hepatectomy. Methods We analyzed all hepatectomy patients with normal and fatty liver texture, between 2014 and 2018 using NSQIP. Main endpoints included perioperative transfusions (within 72 h) and infectious complications. Results A total of 8,237 patients underwent hepatectomy during the study period. The overall rate of fatty liver texture (FLG) was 31% (2,557). Operative duration was significantly long… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 18 publications
0
0
0
Order By: Relevance
“…14 In another analysis of 5337 minor hepatectomies between 2014 and 2018, Villagomez et al found transfusion to be an independent predictor of postoperative infectious complications (P < .05). 3 Previous systematic reviews and single-institution retrospective analyses have found transfusion to be predictive of overall morbidity, major complications, and greater length of stay after hepatectomy. [15][16][17][18] In addition to short-term mortality risk, there is evidence that transfusions may portend poor 90-day survival as well as long-term disease free survival (DFS) and overall survival (OS) after hepatectomy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…14 In another analysis of 5337 minor hepatectomies between 2014 and 2018, Villagomez et al found transfusion to be an independent predictor of postoperative infectious complications (P < .05). 3 Previous systematic reviews and single-institution retrospective analyses have found transfusion to be predictive of overall morbidity, major complications, and greater length of stay after hepatectomy. [15][16][17][18] In addition to short-term mortality risk, there is evidence that transfusions may portend poor 90-day survival as well as long-term disease free survival (DFS) and overall survival (OS) after hepatectomy.…”
Section: Discussionmentioning
confidence: 99%
“…14 In another analysis of 5337 minor hepatectomies between 2014 and 2018, Villagomez et al found transfusion to be an independent predictor of postoperative infectious complications ( P < .05). 3 Previous systematic reviews and single-institution retrospective analyses have found transfusion to be predictive of overall morbidity, major complications, and greater length of stay after hepatectomy. 15-18…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation